ANDROID BASED ADVERTISING REMINDER SYSTEM - Putra, Toni Wijanarko Adi; Saputro, Alif Budi; Solechan, Achmad; Hartono, Budi (Jurnal Transformatika, 2023)
The aim of this research is to introduce an Android-based reminder system that automatically notifies Surya Media Advertising employees of expired leases. Android is a "Linux-based operating system used on mobile devices such as smartphones and tablet computers (PDAs)"[8]. The method used in system development is the SDLC method which is the waterfall model. B. The design step must wait for the completion of the previous step, namely the requirements step. Visual Studio Code and Android Studio are used as software for this research [12]. The results of this study are; 1) Reminder system can help capture rentals for locations faster and easier; 2) The notification function makes it easy to know when the rental period has expired.